Noise Pollution Levels of Commercial Zones in Duhok City (Raparin Journal of Humanities (RJH), 2025)
Environmental pollution has emerged as a critical issue, with noise pollution recognized as a significant environmental concern, its effects being comparable to other forms of pollution. Ecological contamination. Noise pollution presently endangers urban areas due to population growth and technology advancements. Noise pollution is a prevalent and contemporary issue in Duhok city, exacerbated by population growth and urban development stemming from several causes. Due to noise in the research location, we have selected this study as a scientific project involving fieldwork, utilizing a sound level meter. The noise level was assessed in the commercial area at three distinct times: morning, evening, and night. The investigation delineated noise levels in accordance with international criteria for allowed limits, assessing both daytime and nighttime noise and contrasting it with the business area. In a metropolis such as Duhok, noise has surpassed its natural threshold. The maximum average noise level documented in the business zone attained 76 decibels. Noise impacts all inhabitants, resulting in various mental and physical ailments, and there exist numerous therapeutic approaches and advice to address this issue. Mitigating the adverse impacts of noise through the expansion of residential zones, the enactment of environmental legislation, and the promotion of environmental consciousness.